Identifikasi Jenis dan Peranan Kelelawar Buah Penyesap Nira Kelapa di Kecamatan Kokap Kabupaten Kulon Progo - Bambang Agus Suripto; Sumaryanti Sumaryanti; Christian Budi (Jurnal Perlindungan Tanaman Indonesia, 2006)
Although in Kokap Subdistrict Kulon Progo inibitated by four species of fruit bats and Pteropus vampyrus, but it was not known which species visit and suck nira in coconut trees and considered to be pest by villagers. Since the direct technique is not applicable, it is necessary to develop indirect technique to study them. The objectives of this study are to identify the species of fruit bats which visit and suck nira ofcoconut trees using hair characteristics, and to determine the frequencies of their visit to coconut trees. The hair specimen references are collected from the field and from the laboratory collections. The hair specimens are collected from the surface of 750 nira tubes which applied by glued papers and installed in coconut trees as usual in five villages, prepared and identified. The visiting relative frequency is determined by percentage of the number of the tubes with hairs. In the study area are found Macroglossus minimus (Subfamilia Macroglossinae), Cynopterus brachyotis, Cynopterus horsfieldii, Roussetus amplexicaudatus, and Pteropus vampyrus (Subfamilia Pteropodinae). Based on the type and pattern of hair structure, Cynopterus brachyotis and Cynopterus horsfieldii are very difficult to difference each other, meanwhile the other three species are easily identified. Cynopterus brachyotis, Cynopterus horsfieldii, and Roussetus amplexicaudatus were positively visited and sucked the nira of coconut. The visiting frequencies to nira are Cynopterus (C. brachyotis and C. horsefieldii (12, 8%) and R. amplixicaudatus (5,8%). Conceptually, the fruit bats are more properly called them as nuisance animal, and it is not properly called them as pest of nira of coconuts.